Nickel-Catalyzed Reductive Cross-Coupling of Chlorobismuths with Aryl Halides - Liu, Chuanqi; Wang, Xiaoqian; Du, Zhao; Wang, Yilei; Peng, Zhihua (Synthesis, 2025)
A straightforward and efficient method for the synthesis of valuable arylbismuthanes via nickel-catalyzed cross-electrophilic coupling of chlorobismuths with aryl halides has been reported. This cross-electrophile C(sp2)–Bi coupling reaction is conducted under mild reaction conditions and exhibits a broad substrate scope. Notably, the described protocol tolerates various sensitive functionalities including alcohol, nitrile, ester, ketone, and aldehyde. Moreover, the application of the generated arylbismuthanes to the Pd-catalyzed cross-coupling reaction is demonstrated.
Keywords: Cross-electrophilic coupling; Arylbismuthane; Aryl halide; C(sp2)–Bi coupling; Nickel catalyst